Keefektifan Penggunaan Media Video Pembelajaran terhadap Minat dan Prestasi Belajar Matematika pada Materi Baris dan Deret - Sudi Raharjo; Pono Harjo; Eleonora Dwi W (Universitas Kuningan, 2023)
The purpose of this study is to prove: (1) whether the learning achievement of students who are taught using learning video media exceeds the KKM more than 55% with a KKM value of 70. (2) Is there a difference in the learning achievement of students who are taught using video media compared to using e-book media in PDF format. (3) Is there a difference in the level of learning interest of students who are taught using video media compared to using e-book media with PDF format. The populations in this study were students of class XI even semester SMA Negeri 2 Pemalang in the 2020/2021 school year. Sampling used cluster random sampling. The samples taken were one class as Experiment 1 class, one class as Experiment 2 class. The data collection methods used was documentation, tests, and questionnaires. Analysis of the data used is the right-hand proportion test, two-party t-test with a significance level of 5%. The results showed that: (1) students' mathematics learning achievement by being taught using instructional video media obtained more than 55% of students whose scores exceeded the KKM (70). (2) There are differences in the mathematics learning achievement of students who are taught using instructional video media with students who are taught using e-book media in PDF format. (3) There are differences in the interest in learning mathematics of students who are taught using learning video media with students who are taught using e-book media in PDF format.Tujuan penelitian ini adalah untuk membuktikan: (1)apakah prestasi belajar peserta didik yang diajar menggunakan media video pembelajaran yang melampaui KKM lebih dari 55% dengan nilai KKM 70.(2) apakah ada perbedaan prestasi belajar peserta didik yang diajar menggunakan media video dibandingkan dengan menggunakan media ebook dengan format PDF.(3) Apakah ada perbedaan tingkat minat belajar peserta didik yang diajar menggunakan media video dibandingkan dengan menggunakan media ebook dengan format PDF. Populasi dalam penelitian ini adalah peserta didik kelas XI semester genap SMA Negeri 2 Pemalang tahun pelajaran 2020/2021. Pengambilan sampel menggunakan cluster random sampling.Sampel yang diambil sebanyak satu kelas sebagai kelas Eksperimen 1, satu kelas sebagai kelas Eksperimen 2. Metode pengumpulan data yang digunakan adalah dokumentasi, tes, dan angket. Analisis data yang digunakan adalah uji proporsi satu pihak kanan, uji t dua pihak dengan taraf signifikansi 5%. Hasil penelitian menunjukkan bahwa: (1) prestasi belajar matematika peserta didik dengan diajar menggunakan media video pembelajaran memperoleh lebih dari55% peserta didik yang nilainya melampaui KKM (70). (2) terdapat perbedaan prestasi belajar matematika peserta didik yang diajar menggunakan media video pembelajaran dengan peserta didik yang diajar menggunakan media ebook dengan format PDF.(3) terdapat perbedaan minat belajar matematika peserta didik yang diajar menggunakan media video pembelajaran dengan peserta didik yang diajar menggunakan media ebook dengan format PDF..